(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Using a targeted drug delivery system, a medicine’s component is sent straight to the target. The body part (cells, organs, and subcellular layers of a particular group of cells) eliminates the non-specific toxicity of commonly administered medications, thereby depleting essential medications’ effectiveness. The magic bullet concept was developed to achieve this goal, and for more than a century, it has inspired scientists to investigate and reflect. Nanometer-sized devices are referred to as cutting-edge nanomedicine for targeted drug delivery. Various polymers, colloidal (vesicular and multiarticulate), and cellular and subcellular structures for transport have been used and studied. This review discusses the significance and benefits of targeting, as well as its basic principles, methods, and logistics systems. It also focuses on recent developments, problems, and outlooks for the future.